Radiocarbon Dating of the Decorated Cosquer Cave (France). Issue 2 (22nd December 2016) - Valladas, H; Quiles, A; Delque-Kolic, M; Kaltnecker, E; Moreau, C; Pons-Branchu, E; Vanrell, L; Olive, M; Delestre, X
Abstract: The Grotte Cosquer (southeastern France) is a Paleolithic painted cave only accessible by a deep-water dive. The cave has yielded numerous Paleolithic engravings and drawings, which were produced from wood charcoal. This article presents new radiocarbon dates obtained on samples collected in 2012 directly on 17 parietal representations and at the soil surface, and discusses the 14 C results obtained since the discovery of the cave in 1992. A total of 41 samples were dated with ages ranging from 33, 000 to 20, 000 cal BP. They show that the cave was intermittently decorated over about 10, 000 yr.